Proposal For the Implementation of Isak 335 In the Presentation of Financial Reports of Children's Care Institutions (PSAA) Hamzah Ludin - Fitri, Sri Adella; Ramadhani, Ilas; Alhumairo, Kamila; Safitri, Lidia; Amanda, Putri (STIE Tri Bhakti, 2025)
This research aims to identify and improve transparency and accountability in the preparation of financial reports at the Hamzah Ludin Child Social Welfare Institution (PSAA), located at Jl. Kutianyir, Simpang Baringin Tumbang, Kenagarian Kubang, Guguak Subdistrict, Lima Puluh Kota Regency, by referring to ISAK 335. ISAK 335 is a standard that provides guidelines for preparing financial statements for social institutions, which often face challenges in understanding and applying the correct accounting principles. The main issue raised in this study is the difficulty faced by PSAA Hamzah Ludin in preparing financial reports in accordance with ISAK 335, caused by the lack of understanding among the management regarding the correct accounting standards and the relevance of their application in the context of social institutions. The research method used is a qualitative approach, with the primary data collection technique being in-depth interviews with the management of PSAA Hamzah Ludin. The interviews were conducted using two approaches: structured and semi-structured interviews, to explore in more detail the recording and presentation of financial reports at the institution. The findings indicate that despite initial understanding challenges, the implementation of ISAK 335 can improve the quality of financial reports at PSAA Hamzah Ludin. The application of this standard can enhance transparency and accountability, as well as strengthen financial management at the social institution. This study also provides several strategic recommendations, including training for the management on the appropriate accounting standards, to facilitate PSAA Hamzah Ludin in preparing financial reports that are more in line with applicable regulations and improve the overall performance of the institution.